Pengendalian persediaan bahan baku daging babi pada CV Pork King menggunakan metode EOQ - Kevin Moon; Hadisantono; Theodorus B. Hanandoko; Parama Kartika Dewa (Universitas Atma Jaya Yogyakarta, 2026)
[Controlling the pork meat supply at CV Pork King using the EOQ method] CV Pork King is a food industry that offers various types of processed pork meat, ranging from fried pork, roasted pork, wonton noodles, dim sum, spareribs, and satay. The main problem faced by CV Pork King is the occurrence of stock outs for pork meat supplies which have an impact on lost sales. The aim of this research is to reduce stock outs of pork meat so that lost sales do not occur and can reduce total inventory costs by up to 5%. The most suitable method for inventory problems at CV Pork King is the Economic Order Quantity (EOQ) method because it produces optimal inventory costs with lower total costs compared to the current method of CV Pork King. The results of the research demonstrate that by applying the EOQ method to CV Pork King, the total inventory costs incurred for imported pork meat by IDR99,475.80 (a 43.57% reduction from the current inventory system) and for local pork meat by IDR45,594.00 (a 18.20% reduction from the current inventory system).